THE USE OF SPINNING WHEEL MEDIA IN LEARNING TO SPEAK IN THE CLASS X SMAN 6 BONTOA MAROS - Yuliana, Yuliana; Syatriana, Eny; Hijrah (English Language Teaching Methodology, 2024)
This study aims to determine whether there is an influence on the use of spinning wheel media in speaking, especially in the vocabulary and fluency of students in class X Sman 6 Bontoa Maros. This study uses a pre-experimental method to analyze data with a quantitative design. The instruments used were speaking tests and oral tests which consisted of a pre-test, treatment and post-test. The population is students in class X Sman 6 Bontoa Maros and the sample is X MIPA 1 with the use of purposive sampling technique.. This opinion was proven by the results of students' scores in the form of speaking texts, things This can be seen by the higher post-test average scores, namely vocabulary (79.10) and fluency (85.73) compared to the pre-test vocabulary (44.47) and fluency (46.31). Furthermore, there was an increase of 77.0% (vocabulary) and 85.0% (fluency) in learning to use spinning wheel media for six meetings. In addition, the difference in the value of the t-test is higher than the value of the vocabulary t-table (73.262 > 2.101) and fluency (21.075 > 2.101).